EDUKASI KEGAWATDARURATAN STROKE PADA KELOMPOK PROLANIS DI WILAYAH KERJA PUSKESMAS MANGASA KOTA MAKASSAR - Ekowatiningsih , Dyah; Mustafa, Mardiana; Heriansyah, Heriansyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The working area of Mangasa Public Health Center (Puskesmas Mangasa) is located in Makassar City, one of the metropolitan cities in Indonesia with a high population density. Based on data from the Makassar City Health Office, cases of non-communicable diseases (NCDs), including stroke, have shown an increasing trend in recent years. The target partner group in this program is the Chronic Disease Management Program (Prolanis) community, consisting of patients with a history of hypertension, diabetes mellitus, and other comorbidities that place them at high risk for stroke. Data from Puskesmas Mangasa indicate that over the past year, there has been a rise in stroke incidence among members of the Prolanis group. The majority of stroke patients suffer permanent disability due to delays in early treatment. This condition is exacerbated by the community’s limited knowledge of early stroke symptoms and the emergency actions that should be taken before receiving medical care at a health facility.Purpose of the Community Service Activity : To improve the knowledge, skills, and preparedness of the community—particularly Prolanis members—in early detection and emergency management of stroke. Identified Problems : There is a lack of understanding regarding stroke risk factors among the community, especially in recognizing the early signs of stroke using the FAST method (Face, Arm, Speech, Time). Many patients arrive at health facilities after the “golden period” (4.5 hours after stroke onset), resulting in a lower success rate of medical treatment. Proposed Solution : The community service activity is carried out through educational interventions on stroke emergencies. This community-based educational intervention is expected to enhance the knowledge, skills, and readiness of the community in managing stroke emergencies. Expected Outcomes of the Community Service The expected outcome is an increase in community knowledge, particularly among Prolanis members, about the importance of early detection and emergency management of stroke as an effort to reduce disability and mortality rates caused by stroke. Mandatory Output : Publication in a Community Service Journal. Additional Output: Intellectual Property Rights (IPR) registration for the “Stroke Early Detection Educational Flip Card.”Follow-Up Plan : A commitment will be established with the partner organization to ensure sustainability of the community service program.